2007
DOI: 10.1007/s10554-007-9290-0
|View full text |Cite
|
Sign up to set email alerts
|

Angiographically uncertain left main coronary artery narrowings: correlation with multidetector computed tomography and intravascular ultrasound

Abstract: A high degree of correlation was found between MDCT and IVUS regarding the assessment of minimal lumen diameter and area, lumen area stenosis and plaque burden as well as plaque characterization in patients with angiographically borderline LMCA stenosis. Therefore, in patients selected for non-invasive coronary tree evaluation, MDCT may provide a valuable tool for the assessment, decision-making and follow-up of patients with uncertain LMCA disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…These observations are not substantially different from those of a meta-analysis that included 16-and 64-slice MDCT systems [9]. In some studies with native coronary arteries, 16-and 64-slice MDCT systems have been shown to have a good correlation with conventional coronary angiography and IVUS for parameters such as minimum lumen diameter, minimum lumen area, and area stenosis [15,16]. However, there have been few studies of the 64-slice MDCT compared with IVUS for the evaluation of area stenosis of coronary stents.…”
Section: Discussionmentioning
confidence: 58%
“…These observations are not substantially different from those of a meta-analysis that included 16-and 64-slice MDCT systems [9]. In some studies with native coronary arteries, 16-and 64-slice MDCT systems have been shown to have a good correlation with conventional coronary angiography and IVUS for parameters such as minimum lumen diameter, minimum lumen area, and area stenosis [15,16]. However, there have been few studies of the 64-slice MDCT compared with IVUS for the evaluation of area stenosis of coronary stents.…”
Section: Discussionmentioning
confidence: 58%
“…Methods applied for our analysis differ significantly from all of the previous studies exploring the relationship between calcifications and diagnostic accuracy of CTCA, which relied on the suboptimal reference of invasive angiography [1215]. Invasive angiography does not provide optimal stenosis assessment within ostia or bifurcations (a frequent site of coronary calcifications), mainly due to the limited number of projections [1215].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that MSCT and IVUS have similar sensitivity to detect significant and nonsignificant plaques in proximal coronary system [3,23,24]. Furthermore, a high degree of correlation was found between MSCT and IVUS regarding the assessment of minimal lumen diameter and area, lumen area stenosis and plaque burden as well as plaque characterization in patients with angiographically borderline LMCA stenosis [31].…”
Section: Study Limitationsmentioning
confidence: 96%